2017
DOI: 10.1038/srep40462
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Uveal and Capsular Biocompatibility of Hydrophobic Acrylic Intraocular Lens by Surface Grafting with 2-Methacryloyloxyethyl Phosphorylcholine-Methacrylic Acid Copolymer

Abstract: Biocompatibility of intraocular lens (IOL) is critical to vision reconstruction after cataract surgery. Foldable hydrophobic acrylic IOL is vulnerable to the adhesion of extracellular matrix proteins and cells, leading to increased incidence of postoperative inflammation and capsule opacification. To increase IOL biocompatibility, we synthesized a hydrophilic copolymer P(MPC-MAA) and grafted the copolymer onto the surface of IOL through air plasma treatment. X-ray photoelectron spectroscopy, atomic force micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 51 publications
1
17
0
1
Order By: Relevance
“…Chemical shi of protons of methylene and methyl group which were marked with e and f was about 1.3 and 1.8 ppm. The appearances of chemical shi a, b and c at about 2.8, 1.8 and 1.0 ppm, are also in consistent with the reported results 35,36 and demonstrated that HD was graed to the polymer PMMPC because of the existence of the proton of methylene in the PMMPC-HD which was ascribed to the HD.…”
Section: Ftir and 1 H Nmr Of Pmmpc-hdsupporting
confidence: 90%
“…Chemical shi of protons of methylene and methyl group which were marked with e and f was about 1.3 and 1.8 ppm. The appearances of chemical shi a, b and c at about 2.8, 1.8 and 1.0 ppm, are also in consistent with the reported results 35,36 and demonstrated that HD was graed to the polymer PMMPC because of the existence of the proton of methylene in the PMMPC-HD which was ascribed to the HD.…”
Section: Ftir and 1 H Nmr Of Pmmpc-hdsupporting
confidence: 90%
“…The global trend in population aging calls for an increased number of well-trained ophthalmologists to provide eye care to the elderly, who commonly suffer from ophthalmic disorders, including cataract (and intraocular lens-related problems), age-related macular degeneration (AMD), and diabetes retinopathy [15]. Ophthalmic education is essential not only for the training of future ophthalmologists, but also for medical practitioners from other disciplines in general, as visual system dysfunction may provide clues for the diagnosis of systemic diseases [6,7].…”
Section: Introductionmentioning
confidence: 99%
“… 8 Studies from our group and others have reported that hydrophilic surface modification of IOLs can significantly increase protein and cell repellence, thus preventing ACO. 9 , 10 On the other hand, PCO can be suppressed through blocking the migration and proliferation of LECs, which can be achieved by applying cytotoxic drugs or sharpening the optic edge of the IOLs. 11 However, preventative approaches of ACO and PCO are contradictory.…”
mentioning
confidence: 99%